Estudo da riqueza de Hymenoptera (Braconidae: Ichneumonoidea) em áreas de vegetação natural da APA de Descalvado, SP: subsídio para confecção de material paradidático - Cirelli, Kátia Resende Netto (2002)
A survey of the Braconidae (Hymenoptera: Ichneumonoidea) fauna on northwest São Paulo State fragmentary natural environments was conducted using Malaise traps in five sites of Environmental Protected Area of Descalvado, SP, Brazil. A total of 2262 specimens, representing 22 subfamilies and 94 genera, was recovered throughout a period of sixteen months from may 1999 to august 2000. Biological data were obtained from current literature and behavior patterns of host utilization for the studied fauna, in special the Braconidae which have been successful in control of agricultural insect pest. Statistical analyses indicated that the asymptote of current genera richness has been approached using this sampling method. This is the most complete survey available from natural fragmentary areas of the Descalvado Braconidae fauna. Patterns of distribution and richness of the genera of the Braconidae were recovered. Cluster Analysis was adopted taking as attribute the number of Braconidae genera. The flight phenology of these 22 subfamilies of Braconidae was studied and the trap catch for koinobionts peak was in August, 1999 a month before of the idiobionts peak and in June, 2000 both peaks were simultaneous. The phenological peaks of dominant koinobiont taxa (Microgastrinae) were similar to all koinobionts, and the peaks of dominant idiobiont taxa (Doryctinae) were similar to all idiobionts, as well. February, 2000, was the richer month in number of subfamilies (N= 18), corresponding to the same period when the subfamilies wich potencially attack Lepidoptera where collected. The number of females was superior to the number of males and this relation was more accentuated in koinobionts. The peaks of both females and males were similar to dominant koinobiont and idiobiont taxa. Eight new species of the genus Pseudognaptodon Fischer, 1965 (Hymenoptera: Braconidae: Gnamptodontinae) collected in this study were described andillustrated. These information were used to produce the pedagogic material (CD-ROM) which will be distributed in the schools of Descalvado, SP, Brazil, after the training of the teachers.